Forensic Nursing Research: The Basics Explained. Issue 3 (July 2021) - Wickwire, Karin A.; Valentine, Julie L.; Downing, Nancy; Cochran, Courtney Bagents; Drake, Stacy; Sekula, L. Kathleen; Jennings, Sara
Abstract : Supplemental digital content is available in the text. ABSTRACT: As a growing profession, forensic nursing requires research to establish best practice guidelines leading to evidence-based practice. In addition, forensic nursing quality improvement projects are necessary to evaluate and improve practices and policies. The purpose of this article is to provide step-by-step guidelines on research and quality improvement projects to encourage all forensic nurses to actively contribute to and utilize research in practice. Research will expand our forensic nursing science and knowledge base. Ultimately, forensic nursing research will benefit our patients and communities by establishing enhanced, evidence-based care.